Financial Medical Policy: Navigating The Intersection of Accounting, Economics, and Healthcare - Sorongon, Chris G.; Divinagracia, Sheryl S.; Yuesti, Anik; Madrigal, Dennis V.; Devi, Ni Luh Nyoman Sherina (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2026)
Financial medical policy refers to the frameworks and regulations that govern funding, reimbursement, cost management, and financial accountability within healthcare systems. As healthcare costs continue to rise globally, it becomes essential to understand how financial policies, accounting information, budgeting practices, and resource allocation mechanisms influence access to care, quality of services, and overall health outcomes. This research explores the interplay between financial medical policies and healthcare delivery from an accounting-oriented perspective, particularly in relation to cost control, transparency, accountability, and performance-based financing. Using a qualitative literature-based approach, this study analyzes empirical studies, institutional reports, and selected international case examples to identify key issues and policy implications. The discussion highlights that financial reporting, management accounting practices, budgeting systems, and public sector accountability mechanisms can support more effective healthcare governance. The study also emphasizes the importance of value-based care, ethical financial decision-making, health equity, and financial literacy among healthcare providers. Furthermore, this paper proposes recommendations for improving financial medical policies to ensure equitable healthcare access, efficient resource allocation, and sustainable financial management.